PENGARUH GOOD CORPORATE GOVERNANCE DAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP KINERJA KEUANGAN DENGAN MANAJEMEN LABA SEBAGAI VARIABEL MEDIASI (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2018) - Faisal, Ghozy Nur; Syafruddin, Muchamad (Diponegoro Journal of Accounting, 2020)
This study aims to empirically examine the Effect of Good Corporate Governance and Corporate Social Responsibility Mechanisms on Financial Performance with Earnings Management as a Mediating Variable (Empirical Study of Manufacturing Companies Listed on the Indonesia Stock Exchange in 2018). The population in this study are manufacturing companies listed on the Indonesia Stock Exchange in 2018. The sample of this study consisted of 91 companies listed on the Indonesia Stock Exchange (BEI) for the year 2018. The data used in this study were secondary and election data The sample uses a purposive sampling method. The analysis model uses partial least square analysis. The results of this study indicate that the GCG mechanism has a positive effect on financial performance, CSR has a positive effect on financial performance, the GCG mechanism has a negative effect on earnings management, CSR has a negative effect on earnings management, earnings management has a negative effect on financial performance, earnings management can partially mediate the effect of the GCG mechanism on financial performance, and earnings management can mediate partial CSR on financial performance.